Calidad de información transmitida por Enfermería sobre Lactancia Materna, hospital San Vicente de Paúl - Ibarra 2016: Quality of information transmitted by nursing about Breastfeeding, Hospital San Vicente de Paúl - Ibarra 2016 (La U Investiga, 2018)
Breastfeeding supports healthy growth, every mother can breastfeed provided she has good information and support from the Health system. In Ecuador 39.6% of women breastfeed and the average exclusive breastfeeding is 2 and a half months. Nursing through education allows to modify knowledge and practices in individuals. The objective was to determine the quality of breastfeeding information transmitted by the nursing staff at the San Vicente de Paul Hospital. It was a qualitative, non-experimental, observational, descriptive and cross-sectional study. Surveys were applied to patients and nurses, obtaining the following results: predominant age of 20 to 30 years, primiparous mothers, mixed race ethnicity, high school education, married marital status, Ecuadorian nationality, the characteristics of the quality of information transmitted was: timely, understandable and permanent, but not updated and sufficient. Most treated theme: exclusive breastfeeding. Subject less treated benefits of breastfeeding.
Keywords: Information quality; Breastfeeding; Nursing staff